Piros Fehér Zöld - Raffoul, Tarek (Hungary, 2013)
Who will care for a 37-year-old with Down's syndrome when his mother dies? Anna has always been by Laci’s side and took care of him all his life. At 70 however she worries that should anything happen to her there would be nobody left to take care of her son. A short documentary about a mother's struggle to find a right place for her son with Down syndrome.
Film also on HDD Verzio11/12 located: M22 R17 S2 R4
Verzio Film Festival Submission
Keywords: Documentary films